PENERAPAN STRATEGI DIGITAL MARKETING MELALUI INFUENCER PADA UMKM BURGOUTH DI GEGERKALONG BANDUNG - Raden Mochamad Raka Boedianto; Ady Tia Ramadhan (JURNAL MANAJEMEN MODAL INSANI DAN BISNIS (JMMIB), 2025)
This study explores the effectiveness of digital marketing strategies and the role of influencers in increasing product sales for small businesses in the context, using the local fast-food brand "Burgouth" in Bandung as a case study. Employing a qualitative approach, data were gathered through interviews, observations, and documentation. The findings indicate that social media platforms such as Instagram and TikTok significantly enhance audience reach and help establish a strong brand image. Collaborations with influencers were shown to improve consumer trust and purchasing interest, particularly when aligned with the audience’s lifestyle. Diverse content strategies— including educational, promotional, and entertaining materials also contributed to higher engagement and brand awareness. The study concludes that a well targeted market approach, effective use of digital platforms, and strategic influencer partnerships are essential for the success of digital marketing initiatives among small businesses in today’s digital era. Keywords: Digital Marketing